Modal And FRF Based Updating Methods For The Investigation Of The Dynamic Behaviour Of A Plate / Mohd Syazwan Mohd Zin ...[et al.] - Mohd Zin, Mohd Syazwan; Abdul Rani, Muhamad Norhisham; Yunus, Mohd Azmi; Wan Iskandar Mirza, Wan Imaan Izhan; Mat Isa, Ahmad Azlan; Mohamed, Zulkifli (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Accurate finite element models of engineering structures are of paramount importance to dynamicists to be used in predicting the dynamic behaviour of the structures. In order to have a finite element model that can accurately predict the structural behavior, measured data obtained from the test structure can be used to reconcile the finite element model and the procedures involved the reconciliation is model updating. The model updating methods, in general, are classified into two different classes which are the modal based updating and frequency response function (FRF) based updating. This research was aimed to investigate the efficiency, accuracy and economics between the FRF based and the Modal based updating on a thin aluminium plate structure. In this study, the measured results from the structure were obtained from the Experimental Modal Analysis (EMA) via LMS SCADAS. The structure was tested using an impact hammer and roving accelerometers. The test was performed under free-free boundary conditions. The initial finite element model of the aluminum plate was constructed and improved using both model updating methods. Then, the initial finite element results were compared with the experimental results for validation. The comparison of results revealed that the Modal based updating showed better capability to be used in reconciling the FE resonance frequencies to the measured counterparts with 6.02 percent of reduction in total error in comparison with the FRF based updating with 8.39 percent. Meanwhile, FRF based updating recorded much better capability to match the FE excitation and resonance frequencies with the measured ones.